ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, RASIO SOLVABILITAS, DAN RASIO PROFITABILITAS PADA PT SIDO MUNCUL TBK PERIODE 2012-2021 - Permana Putra, Nanda; Syakhrial (Journal of Research and Publication Innovation, 2024)
This research aims to find out the Liquidity Ratio, Solvency Ratio and Profitability Ratio as well as to find out the financial performance of PT Sido Muncul Tbk for the 2012-2021 period which is assessed using the Liquidity Ratio, Solvency Ratio and Profitability Ratio. The method used in this research is a quantitative descriptive method, namely research data in the form of numbers and the research results are then presented in writing by the author. The results of this research show that the Liquidity Ratio at PT Sido Muncul Tbk for the 2012-2021 period shows a healthy condition, because the average value of the (CR) is 599%, (QR) 513%, (CAR) 309% which is a criterion above the industry standard, namely 200%. The Solvency Ratio at PT Sido Muncul Tbk for the 2012-2021 period shows a healthy condition, because the average value of the (DAR) is 13.5% and the (DER) is 17.6%, which are above standard criteria. industry, namely 35%. The Profitability Ratio at PT Sido Muncul Tbk for the 2012-2021 period shows a not healthy condition, because the average value of (ROA) is 187%, and also (ROE) shows an unhealthy condition because the average value of (ROE) 22.7% which does not meet industry standards of 40%. For the financial performance of PT Sido Muncul Tbk for the 2012-2021 period which is assessed using Liquidity Ratios, Solvency Ratios and Profitability Ratios, it shows an efficient or healthy condition, because seen from the average values of Liquidity Ratios, Profitability Ratios, Solvency Ratios are above industry standards , namely 599% for Cash Ratio, 513% for (QR), 309% for (CAR), (DAR) 13.5%, (DER) 17.6%. Meanwhile, the Profitability Ratios in (ROE) and (ROA) show unhealthy or less efficient conditions, because the average values do not meet industry standards.